2020
DOI: 10.1002/ijc.32945
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative, qualitative and spatial analysis of lymphocyte infiltration in periampullary and pancreatic adenocarcinoma

Abstract: Immunotherapeutic modalities are currently revolutionizing cancer treatment. In pancreatic cancer, however, early clinical trials have been disappointing. The optimization of immunotherapeutic strategies requires better understanding of the inflammatory tumor microenvironment. Therefore, the aim of our study was to perform a detailed in situ description of lymphocyte infiltration patterns in resected pancreatic and other periampullary cancers. Multiplexed immunofluorescence imaging was applied to tissue microa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 52 publications
4
37
0
1
Order By: Relevance
“…NKT cells were more abundant in APC mutated tumors, which may well be explained by the fact that APC mutations were exclusively found in I-type tumors in the current cohort (4). The significantly lower infiltration of CD68 + macrophages in CDKN2A mutated tumors is in line with findings for other types of immune cells (12,22), but may also merely be due to the fact that CDKN2A mutations are more common in PBtype tumors (4). Moreover, in the present study, mDC infiltration was found to be higher in SMAD4 wt tumors, which is in line with a previous study using a different method to assess both immune cell infiltration and mutational status (23).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…NKT cells were more abundant in APC mutated tumors, which may well be explained by the fact that APC mutations were exclusively found in I-type tumors in the current cohort (4). The significantly lower infiltration of CD68 + macrophages in CDKN2A mutated tumors is in line with findings for other types of immune cells (12,22), but may also merely be due to the fact that CDKN2A mutations are more common in PBtype tumors (4). Moreover, in the present study, mDC infiltration was found to be higher in SMAD4 wt tumors, which is in line with a previous study using a different method to assess both immune cell infiltration and mutational status (23).…”
Section: Discussionsupporting
confidence: 92%
“…The results demonstrate that high infiltration of several immune cell populations, especially NKT cells, was significantly associated with favorable clinicopathological factors, which is in line with previous findings regarding T and B lymphocytes (12).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These findings suggest that CLEC3B may play an important role in immune infiltration of SCC. The correlations between CLEC3B and immune markers of immune cells (selected by investigating some relevant papers [27][28][29][30][31]) were analyzed in the TIMER database to explore the relationship between CLEC3B and immune infiltrating cells of ADC and SCC (Table 6). In SCC, CLEC3B expression was positively correlated with majority of gene markers of different functional T cells (CD8+ T, Th1, Th2, etc.…”
Section: Clec3b Expression Is Associated With Immune Infiltration In mentioning
confidence: 99%